Orofacial granulomatosis in children: think about Crohn's disease. - Lazzerini, Marzia; Martelossi, Stefano; Cont, Gabriele; Bersanini, Chiara; Ventura, Giovanna; Fontana, Massimo; Zuin, Giovanna; Ventura, Alessandro; Taddio, Andrea (Dig Liver Dis, 2015)
BACKGROUND: The term orofacial granulomatosis is conventionally used to describe patients with granulomatous lesions affecting the orofacial tissues, in absence of intestinal lesions. Lip swelling and facial swelling are the most common clinical signs. Despite the fact that histologically it is not distinguishable from Crohn's disease, and that both diseases have a chronic/recurrent course, the relationship between orofacial granulomatosis and Crohn's disease is still debated. METHODS: Herein we present five cases of orofacial granulomatosis. RESULTS: All patients presented concomitant Crohn's disease, supporting the hypothesis that orofacial granulomatosis and Crohn's disease may be one single disease. Thalidomide was effective in inducing remission of oral and intestinal symptoms in all five cases and could be considered a valid treatment opportunity for these patients. CONCLUSIONS: Orofacial granulomatosis and Crohn's disease may be part of the same disease; both may respond to thalidomide.
Keywords: Adolescent; Biopsy; Child; Colonoscopy; Crohn Disease; Diagnosis, Differential; Female; Granulomatosis, Orofacial; Humans; Immunosuppressive Agents; Male; Thalidomide